Cadherin-11 Is Required for Neural Crest Specification and Survival - Manohar, Subrajaa; Camacho-Magallanes, Alberto; Echeverria, Camilo; Rogers, Crystal D. (Frontiers in Physiology, 2020)
Neural crest (NC) cells are multipotent embryonic cells that form melanocytes, craniofacial bone and cartilage, and the peripheral nervous system in vertebrates. NC cells express many cadherin proteins, which control their specification, epithelial to mesenchymal transition (EMT), migration, and mesenchymal to epithelial transition. Abnormal NC development leads to congenital defects including craniofacial clefts as well as NC-derived cancers. Here, we identify the role of the type II cadherin protein, Cadherin-11 (CDH11), in early chicken NC development. CDH11 is crucial for NC cell migration in amphibian embryos and is linked to cell survival, proliferation, and migration in cancer cells. It has been linked to the complex neurocristopathy disorder, Elsahy‐Waters Syndrome, in humans. Using immunohistochemistry (IHC), we determined that CDH11 protein has dynamic expression that is first co-localized with neural progenitors in early embryos and subsequently upregulated specifically in NC cells as they are specified in the dorsal neural tube prior to migration. We identified that loss of CDH11 led to a reduction of bonafide NC cells in the dorsal neural tube combined with defects in cell migration and survival. Loss of CDH11 increased p53-mediated programmed-cell death, and blocking the p53 pathway rescued the NC phenotype. Our findings demonstrate an early requirement for CDH11 in NC development, and may increase our understanding of early cadherin-related NC developmental defects.